Modeling and optimization of general cargo port operations through fuzzy minimal spanning tree and fuzzy dynamic programming approaches - Oenuet, Semih; Saglam, Canan Oelcer (ICIC INTERNATIONAL, 2008)
General cargo handling is of special importance because it generally corresponds to most of the costs incurred by the loading and unloading of ships at port. This study addresses the loading process of general cargo-type export products. The theoretical structure of a general port optimization model is described, and an optimization model is applied to a general cargo port located at the Marmara Sea in Turkey as a real-world case study. The main objective of this study is to display the methodology for increasing the ship loading rate. The present ship loading rate is, measured as a baseline, and the factors that affect the baseline loading performance are identified. Simulation and statistical techniques such as hypothesis tests and correlation analyses are used to optimize equipment and verify variables. The problem is solved with minimal spanning tree and dynamic programming models. These models are integrated with fuzzy methods to tackle uncertainties in the data. The results of the models are compared, and sensitivity analysis is applied to each mathematical model.
Keywords: general cargo; ports; transportation management; fuzzy sets; fuzzy minimal spanning tree; fuzzy dynamic programming; simulation; SYSTEM; Computer Science